Enunciação e atividade de linguagem. O substantivo comum: estudo de caso e propostas com vistas à prática de ensino - Fujisaka, Larissa Cella Hirai [UNIFESP] (2020)
Enrolled in the field of Enunciation Linguistics, this work aims to analyze the enunciative functioning of the KEY noun in Brazilian Portuguese, and thus contribute to studies focused on the enunciative base linguistic description and the (re) thinking of teaching practices in what it concerns the class of nouns. For this, we propose to retrace, in the linguistic system, regularities of functioning specific to the language activity that, constituting the semantics of the form to be analyzed, support different values in its different uses. The search for such regularities in its developments leads to a reexamination of semantic properties that are commonly attributed to it. From this point of view, the study aims to better understand the potential referencing of the noun, more specifically, how its own semantism allows to understand, on the one hand, the different values it acquires when enunciating, on the other, the ways in which these values are established in relation to the context. This results in a more in-depth examination of the subclassification of the semantic base of concrete-abstract, commonly grounded in traces of vocabulary meaning to be subverted or not in the discursive process. The investigation has as a theoretical-methodological framework the Theory of Predicative and Enunciative Operations, with emphasis on the studies of Franckel (2002), De Vogüé, Franckel and Paillard (2011) and De Vogüé (2013), which deal with issues related to semantic identity and principles of variation in languages from the perspective of the enunciative approach in question.